Pengaruh Model Pembelajaran Scramble Berbantuan Make A Match Terhadap Motivasi Belajar dan Hasil Belajar Peserta Didik Kelas X pada Materi Struktur Atom - Ramadanti, Wicahni; Fikroh, Retno Aliyatul (Jurnal Penelitian Pendidikan IPA, 2024)
Abstract and complex learning materials presented with monotonous models can lead to decreased motivation and suboptimal learning outcomes due to student boredom. This study aims to determine the effect of the make-a-match assisted scramble learning model on grade X students' learning motivation and learning outcomes on atomic structure material. The research method was quasi-experimental with a nonequivalent pretest-posttest control group design. The research location at A Sleman High School for the 2023/2024 academic year uses two research samples: class XC as an experimental class and class XG as a control class. The sampling technique used is cluster random sampling. Data were collected using learning motivation questionnaires and test questions. The Mann-Whitney test was applied to analyze the data, revealing significance values of 0.045 and 0.000, both below the 0.05 threshold. The results indicate that the make-a-match assisted scramble learning model significantly enhances learning motivation and outcomes for class X students on atomic structure material.